Database Design and SQL for DB2. - Cooper, James (MC Press, 2013)
Thorough and updated coverage of database design and SQL for DB2 are the focus of this guide for the relational database-management system used on IBM i computer systems. Suitable for classroom instruction or self-study, this book explains the most widely used database language and the way that language is implemented on a variety of computer platforms. Topics covered include database concepts, SQL inquiries, web applications, and database security, and the material is reinforced by numerous illustrations, examples, and exercises.